Assessment of soil-water vulnerability to salinization in Ben Tre Province using DRASTIC model - Thanh, Le Ngoc; Dao, Van Tuyet; Lam, Van Tan; Nguyen, Quang Dung; Luu , Hai Tung (Vietnam Journal of Marine Science and Technology, 2023)
Soil water in the coastal zones is more vulnerable to salinization. Soil-water vulnerability assessment is an effective tool for soil-water management. This study used the DRASTIC model, which is based on seven factors viz: depth to soil water, recharge, soil-water bearing layer, soil media, topography, impact of root zone, and hydraulic conductivity to evaluate soil-water salinization potentiality of Ben Tre Province. The obtained soil-water vulnerability map is divided into three vulnerable zones: low vulnerability zone with 348.59 km2 of total area, moderate vulnerability zone with 1898.77 km2, and high vulnerability zone having 147.64 km2. Moreover, the DRASTIC model was validated by Total dissolved solids (TDS) over the study area. Validation results showed the low vulnerability zone of the moderate saline (TDS = 1,500–7,000 mg/L), while the moderate vulnerability zone of the moderate, high, and very high saline (TDS = 1,500–35,000 mg/L). However, the high vulnerability zone has a very high saline (TDS = 15,000–35,000 mg/L). The study results are of considerable value to land use planning and soil researchers.